Weighted Finite-State Methods for Spell-Checking and Correction - Pirinen, Tommi (Helsingin yliopisto, 2014)
This dissertation is a large-scale study of spell-checking and correction using finite-state technology. Finite-state spell-checking is a key method for handling morphologically complex languages in a computationally efficient manner. This dissertation discusses the technological and practical considerations that are required for finite-state spell-checkers to be at the same level as state-of-the-art non-finite-state spell-checkers. Three aspects of spell-checking are considered in the thesis: modelling of correctly written words and word-forms with finite-state language models, applying statistical information to finite-state language models with a specific focus on morphologically complex languages, and modelling misspellings and typing errors using finite-state automata-based error models. The usability of finite-state spell-checkers as a viable alternative to traditional non-finite-state solutions is demonstrated in a large-scale evaluation of spell-checking speed and the quality using languages with morphologically different natures. The selected languages display a full range of typological complexity, from isolating English to polysynthetic Greenlandic with agglutinative Finnish and the Saami languages somewhere in between. Tässä väitöskirjassa tutkin äärellistilaisten menetelmien käyttöä oikaisuluvussa. Äärellistilaiset menetelmät mahdollistavat sananmuodostukseltaan monimutkaisempien kielten, kuten suomen tai grönlannin, sanaston sujuvan käsittelyn oikaisulukusovelluksissa. Käsittelen tutkielmassani tieteellisiä ja käytännöllisiä toteutuksia, jotka ovat tarpeen, jotta tällaisia sananmuodostukseltaan monimutkallisempia kieliä voisi käsitellä oikaisuluvussa yhtä tehokkaasti kuin yksinkertaisempia kieliä, kuten englantia tai muita indo-eurooppalaisia kieliä nyt käsitellään. Tutkielmassa esitellään kolme keskeistä tutkimusongelmaa, jotka koskevat oikaisuluvun toteuttamista sanarakenteeltaan monimutkaisemmille kielille: miten mallintaa oikeinkirjoitetut sanamuodot äärellistilaisin mallein, miten soveltaa ...